2011
DOI: 10.1002/ppap.201100070
|View full text |Cite
|
Sign up to set email alerts
|

Tetraethyl Orthosilicate and Acrylic Acid Forming Robust Carboxylic Functionalities on Plastic Surfaces for Biodiagnostics

Abstract: properties of film that is formed as a result of sequential, plasma assisted fragmentation and deposition of vapours of acrylic acid and tetraethyl ortho silicate (TEOS). In this context, TEOS serves as an adhesion layer to the plastic substrate and also as a network-building layer for further cross-linking with acrylic acid. The presence of silanols (Si-OH) can facilitate large uptake of water molecules and cause significant hydration of the layer, which in combination with high total negative charge lowers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The polymerization process is initialized and assisted by plasma and results into a fabrication of relatively homogeneous layer with high density of carboxylic acids. The very low water contact angle of the film is also suggesting that TEOS might be inserted into the sensing -COOH layer, cross linking the polymerized AA molecules and forming abundance of silanols and silyl-ethers [26].…”
Section: Preparation Of Sensing Substratementioning
confidence: 99%
“…The polymerization process is initialized and assisted by plasma and results into a fabrication of relatively homogeneous layer with high density of carboxylic acids. The very low water contact angle of the film is also suggesting that TEOS might be inserted into the sensing -COOH layer, cross linking the polymerized AA molecules and forming abundance of silanols and silyl-ethers [26].…”
Section: Preparation Of Sensing Substratementioning
confidence: 99%
“… 12 The role of siloxane in anchoring to the plastic and metal surfaces for further plasma functionalization and cross-linking has been established previously. 25 , 26 We carried out the amine functionalization using APTES as the precursor material, since the adhesion of the functionalized coating to the cellulose fibers is critical for repeatable and reproducible bioassay performance. The schematic for binding of APTES to cellulose is shown in Figure 1 c. The deposition time was fixed at 20 s, and no systematic variation was performed to study the effect of deposition time on surface functionalization and DNA hybridization.…”
Section: Resultsmentioning
confidence: 99%
“…Surface amination of polymer substrates by plasma-enhanced chemical vapor deposition (PECVD) is routinely carried out using allylamine, ammonia, and nitrogen/hydrogen gases. , In low-pressure PECVD, APTES has an advantage over alkyl amine in determining the extent of amination and adhesion strength to surfaces upon rigorous washing . The role of siloxane in anchoring to the plastic and metal surfaces for further plasma functionalization and cross-linking has been established previously. , We carried out the amine functionalization using APTES as the precursor material, since the adhesion of the functionalized coating to the cellulose fibers is critical for repeatable and reproducible bioassay performance. The schematic for binding of APTES to cellulose is shown in Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, some studies have reported that the CC bonds of acrylic acid (AA) are easily attached to silanol groups at the surface of nanosized SiO 2 which would promote the coating process . The encapsulation of acrylamide (AM) on SiO 2 particles can also be driven by the hydrogen‐bonding interaction between the hydroxyl group on the surface of SiO 2 core and the amide unit of AM during the polymerization .…”
Section: Introductionmentioning
confidence: 99%